2023
DOI: 10.1186/s12889-023-15415-2
|View full text |Cite
|
Sign up to set email alerts
|

Health litigation and cancer survival in patients treated in the public health system in a large Brazilian city, 2014–2019

Abstract: Background Litigation for health care, also known as health judicialization, is frequent in Brazil. It involves recourse to the court system to access health services. The study aimed to evaluate whether cancer patients in Belo Horizonte, Minas Gerais, Brazil, increased their overall survival by increasing access to certain drugs or treatments through litigation, controlling for the effect of demographic and disease-related variables. Methods A ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Diagnostic practices need to establish mechanisms that encompass symptom profiles that are widely shared across populations and disorders (with regard to psychopathology), but others are more specific to one or a set of forms of psychopathology ( 53 55 ). The severity of symptoms and treatment time in certain regions may indicate the need for specific services for certain locations ( 54 56 ). As an example, the current sample indicated that diagnosis and treatment time are related, thereby reinforcing the need for a biopsychosocial model.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic practices need to establish mechanisms that encompass symptom profiles that are widely shared across populations and disorders (with regard to psychopathology), but others are more specific to one or a set of forms of psychopathology ( 53 55 ). The severity of symptoms and treatment time in certain regions may indicate the need for specific services for certain locations ( 54 56 ). As an example, the current sample indicated that diagnosis and treatment time are related, thereby reinforcing the need for a biopsychosocial model.…”
Section: Discussionmentioning
confidence: 99%